1, 2, 3‐Tri(9‐anthryl)benzene: Photophysical Properties and Solid‐State Intermolecular Interactions of Radially Arranged, Congested Aromatic π‐Planes. Issue 5 (3rd January 2022) - Nishiuchi, Tomohiko; Sotome, Hikaru; Shimizu, Kazuto; Miyasaka, Hiroshi; Kubo, Takashi
Abstract: We report the Negishi coupling based synthesis of 1, 2, 3‐tri(9‐anthryl)benzene derivatives containing three radially arranged anthracenes in a π‐cluster. In the crystalline state of the unsubstituted derivative, intermolecular π–π and CH–π interactions between the anthracene units drive the formation of the two‐dimensional packing structure. Owing to though‐space π‐conjugation between anthracene units, the substances have unique electronic properties. The excited‐state dynamic behavior occurring between the three anthracene moieties, such as exciton localization/delocalization, was elucidated by means of transient absorption measurements and quantum chemical calculations. Interestingly, even though the three anthracenes are closely oriented with approximately 3.0 Å between their C‐9 positions, exciton localization on two anthracene units is energetically favorable because of the flexible nature of the radially arranged aromatic rings. Abstract : Anthracene congestion : 1, 2, 3‐Tri(9‐anthryl)benzene derivatives containing radially shaped π‐clusters were constructed by using Pd I ‐catalyzed Negishi coupling reactions. The presence of π‐congestion as well as intermolecular π–π and CH–π interactions between anthracene units in the crystalline state gives these substances unique electronic properties. The excited‐state dynamics associated with the radially arranged π‐system were elucidated by using transient absorption measurements.